Cultivating The Future: The Importance of Entrepreneurship Education in South Africa’s Basic Education Sector - Mlambo, Victor H; Mbongwa, Lethiwe; Khambule, Thandiwe (Cita Konsultindo Research Center, 2024)
This paper examines the importance of entrepreneurship education in South Africa's primary education sector. The paper argues that the consolidation of entrepreneurship education at primary and high school levels in South Africa can contribute to socio-economic development but also help address issues such as poverty inequality and youth unemployment. This paper employed Schumpeter's Theory of Innovation and the Need for Achievement Theory as a theoretical lens. A systematic literature review was employed as a research approach in this paper. Five databases were used to search for data. The paper revealed that entrepreneurship education had not been fully consolidated in South Africa's primary education sector, significantly depriving learners of innovative skills and competencies to help them become entrepreneurs tomorrow. The paper recommends that the government accelerate the inclusion of entrepreneurship as a standalone subject in the primary education sector so that by the time learners graduate from high school and enter university, they have a deep understanding of entrepreneurship, which increases their chances of becoming entrepreneurs, thus contributing to the country's socio-economic development.